Analisis Sustainability Report pada Perusahaan PT. XYZ di Karawang - Ami Yuliastuti; Lilis Lasmini; Rohma Septiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In Companies today must be able to actively participate in sustainable development. The effort to publish a sustainability report is one of the strategies to implement sustainable development in a transparent and measurable manner. The purpose of this study is to analyse the disclosure of sustainability reports in the company. This research was conducted qualitatively. The type of data used is documentary data and the data source is secondary data. The data source can be a sustainability report from a manufacturing company at company XYZ. The data collection method used in this research is the interview method. The object of this research is PT XYZ in Karawang. The researcher conducted an analysis using the content analysis method based on the disclosure/reporting rules that should be implemented in accordance with the Sustainability Reporting Guideline and the Global Reporting Initiative (GRI) Guidelines. The GRI provides a standardised corporate reporting framework on how to disclose economic, environmental, social and corporate governance issues in preparing financial statements.